Degeneration of the Sensorimotor Tract in Degenerative Cervical Myelopathy and Compensatory Structural Changes in the Brain - Chen, Senlin; Wang, Ying; Wu, Xianyong; Chang, Jianchao; Jin, Weiming; Li, Wei; Song, Peiwen; Wu, Yuanyuan; Zhu, Jiajia; Qian, Yinfeng; Shen, Cailiang; Yu, Yongqiang; et al. (Frontiers in Aging Neuroscience, 2022)
Degenerative cervical myelopathy is a progressive neurodegenerative disease, that has become increasingly prevalent in the ageing population worldwide. The current study determined the factors affecting degeneration in sensorimotor tract with degenerative cervical myelopathy and its relationship with brain structure. We divided patients into hyperintensity (HS) and non-hyperintensity (nHS) groups and measured the fractional anisotropy and apparent diffusion coefficients of the lateral corticospinal tract (CST), fasciculus gracilis and fasciculus cuneatus (FGC). Voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) techniques were used to estimate brain structure changes. Correlation of the modified Japanese Orthopaedic Association (mJOA) score, light touch, pinprick, motor score and FA ratios of the CST at different levels were analysed. Compared to healthy controls, the FA ratios of CST in the HS and nHS groups were decreased at all levels, and the ADC ratio was increased only at C4/5 levels in the HS group. The FA ratio of FGC was decreased at the C3/4 and C4/5 levels in the HS group and only decreased at the C4/5 level in the nHS group. The ADC ratio was decreased only at the C4/5 level in the HS group. VBM analysis revealed that the volume of the precentral gyrus, postcentral gyrus and paracentral lobule increased in patients compared to controls. TBSS analysis found no statistical significance between the sensory and motor tracts in white matter. The volume of clusters in HS and nHS groups negatively correlated with the C1/2 FA ratio of the CST. The results showed that the degeneration distance of the CST was longer than the FGC, and the degeneration distance was related to the degree of compression and spinal cord damage. Structural compensation and the neurotrophin family may lead to enlargement of the brain.